Results of a Study Comparing Glycated Albumin to Other Glycemic Indices - Desouza, Cyrus V; Holcomb, Richard G; Rosenstock, Julio; Frias, Juan P; Hsia, Stanley H; Klein, Eric J; Zhou, Rong; Kohzuma, Takuji; Fonseca, Vivian A (The Journal of Clinical Endocrinology & Metabolism, 2020)
Abstract Context Intermediate-term glycemic control metrics fulfill a need for measures beyond hemoglobin A1C. Objective Compare glycated albumin (GA), a 14-day blood glucose measure, with other glycemic indices. Design 24-week prospective study of assay performance. Setting 8 US clinics. Participants Subjects with type 1 (n = 73) and type 2 diabetes (n = 77) undergoing changes to improve glycemic control (n = 98) or with stable diabetes therapy (n = 52). Interventions GA, fructosamine, and A1C measured at prespecified intervals. Mean blood glucose (MBG) calculated using weekly self-monitored blood glucose profiles. Main Outcome Measures Primary: Pearson correlation between GA and fructosamine. Secondary: magnitude (Spearman correlation) and direction (Kendall correlation) of change of glycemic indices in the first 3 months after a change in diabetes management. Results GA was more concordant (60.8%) with changes in MBG than fructosamine (55.5%) or A1C (45.5%). Across all subjects and visits, the GA Pearson correlation with fructosamine was 0.920. Pearson correlations with A1C were 0.655 for GA and 0.515 for fructosamine (P < .001) and with MBG were 0.590 and 0.454, respectively (P < .001). At the individual subject level, Pearson correlations with both A1C and MBG were higher for GA than for fructosamine in 56% of subjects; only 4% of subjects had higher fructosamine correlations with A1C and MBG. GA had a higher Pearson correlation with A1C and MBG in 82% and 70% of subjects, respectively. Conclusions Compared with fructosamine, GA correlates significantly better with both short-term MBG and long-term A1C and may be more useful than fructosamine in clinical situations requiring monitoring of intermediate-term glycemic control (NCT02489773).